Drug-Food Interactions: The Hidden Frontier in Clinical Practice - Muhammad Saleh Faisal (Journal of Gandhara Medical and Dental Sciences, 2025)
A drug interaction is a situation in which a substance affects the activity of a drug, i.e., the effects are either increased decreased, or a new effect is produced that neither substance causes on its own.1 It represents an important source of medication errors.2 In contemporary clinical practice, drug-drug interactions (DDIs) are a well-established concern, and there are protocols, alerts, and clinical guidelines in place to reduce harm.3 In contrast, drug-food interactions (DFIs) have long been under-recognised and frequently overlooked in pharmacotherapy. Several factors contribute to the neglect of Development Finance Institutions (DFIs). Firstly, DFIs receive little attention in most clinical medicine curricula. While students are trained to screen for DDIs, few are taught about DFIs. Secondly, most electronic medical record systems and pharmacy software offer limited or weak alerts for drug-food interactions. This creates a blind spot in prescribing and dispensing practices. Thirdly, clinical workloads and time constraints often prevent clinicians and pharmacists from providing dietary guidance. Moreover, significant food effects complicate the development of new drugs, especially when clinical plans require controlled or monitored food intake during dosing. So, predicting whether a drug or its product will exhibit a food effect in humans remains a challenge.